(untitled) (Journal of Applied Learning and Teaching, 2023)
This research was conducted with the purpose of analyzing the learning styles in online environments of students in the Anadolu University Institute of Social Sciences distance education non-thesis Master’s program. To this end, a quantitative cross-sectional screening model was applied to a total of 271 students in the distance education non-thesis Master’s degree program. The data for the study was gathered online using the “E-Learning Styles Scale for Electronic Environments”. Some of the findings of the study are as follows: (1) The learning styles in online environments of students do not show statistically significant differences based on sex, income, and average daily use of technological devices. (2) Age appears to have a high level of influence on the visual and aural learning levels of students in online environments and a medium level of influence on their active learning levels. (3) Students who are retired have lower levels of audiovisual learning and active learning compared to students in other vocational groups. (4) As the technology use efficacies of students increase, their logical learning levels in online environments increase. (5) Students who use technological devices for an average of seven or more hours per day have higher independent learning levels in online environments compared to those who use them between 0-3 hours.